A diary without the I: embodiment and self-construction in Felix Hartlaub's extrospective Second World War Paris writings. Issue 7 (2nd July 2020) - Roseau, Katherine
ABSTRACT: In this article, I study identity construction in a diary that is not dependent on an inward-focus or first-person pronouns. Felix Hartlaub, a German occupier in Paris in 1941, kept a diary that pushes us to reconsider the boundaries of the genre. Hartlaub consistently uses the third person in his diary to create a version of his self, a doppelganger of the author, whom he calls simply ' er ' ('he'). A nascent writer, a historian, and a Francophile, Hartlaub failed to find a desirable role for himself with his colleagues or among the 'cold' Parisian strangers. His focus is outward, on his new external space, including the occupied Parisians who populate it. A particular corporeal style impregnates his text as he relates mostly non-verbal, gestural interactions between Parisians and the doppelganger. Drawing on cognitive and embodiment studies, I argue that understanding the self arises from interactions with others, and therefore extrospective texts must not be excluded from the diary genre. This study suggests that wartime diarists internalise their external space, including body language of others, to negotiate a new identity, which appears fragmented and detached in the text.